ABAGEREZI :Embodiment and separation at source studied through the lens of everyday informal street reclaiming in Johannesburg - Shogole, Manape Precious (My University, 2019)
This research report is an ethnographic study of the everyday work-life of informal street reclaimers from Bekezela in Newtown, Johannesburg. The focus is on seven black male reclaimers and one black female reclaimer who informally salvage recyclable materials from rubbish bins and sell them to buy-back centers (BBC) to earn a living. The Bekezela reclaimers start work at 3:30 am, walking far distances in the darkness to reach the wealthy suburbs that are the richest source of recyclables. While it is often assumed that reclaimers are fiercely independent, the research found that these reclaimers who live together in Belezela ended up reclaiming together. They also formed the Royals and Bekezela Plus (informal organisations studied in this report) to create social and economic security and stability. These organisations were developed over time to build trust, loyalty and accountability. By following the daily, embodied work of the eight Bekezela reclaimers, the report develops a nuanced understanding reclaimers as complex people who develop social relations and associations as they conduct complex work that entails multiple areas of specialization learned from each other in the streets. Without any attention to this rich social world, Johannesburg’s Pikitup waste management utility implemented a separation at source (S@S) programme that pays private companies to do the same work as reclaimers. Having illuminated the rich social life of reclaimers, the report is then able to analyse the multiple ways that the city’s S@S programme disrupts their social world. The report argues that the S@S programme undermines the ability of informal reclaimers to pursue their work and life projects without providing any credible alternatives. The report concludes by exploring how reclaimers in Bekezela, together with reclaimers from across the city who are members of the African Reclaimers Organisation (ARO), are contesting S@S and mobilizing for an approach to S@S that recognizes, builds on and strengthens their life projects. At the same time, the report identifies how the 8 reclaimers do not necessarily have interest or faith in this type of more formal organization.
research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Anthropology, September 2019